2009
DOI: 10.1002/app.30076
|View full text |Cite
|
Sign up to set email alerts
|

Dynamically vulcanized blends of polypropylene and ethylene‐octene copolymer: Comparison of different peroxides on mechanical, thermal, and morphological characteristics

Abstract: Thermoplastic vulcanizates (TPVs) are prepared by the dynamic vulcanization process, where crosslinking of an elastomer takes place during its melt mixing with a thermoplastic polymer under high shear. TPVs based on polypropylene (PP) with different grades of ethylene-octene copolymers (EOC) were prepared with a coagent assisted peroxide crosslinking system. The effect of dynamic vulcanization and influence of various types and concentrations of peroxide were mainly studied on the basis of the mechanical, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…This study reveals the positive influence of the EIReP in the preparation of TPVs and paves a new technology for the development of various types of TPVs in an eco‐friendly direction. The authors' earlier work reported the influence of three different peroxides36 and different co‐agents37 on 30:70 blend ratio of peroxide cured PP/EOC TPVs. The readers can refer the results of peroxide‐based TPVs to understand the divergence in the performance properties and morphological evolution.…”
Section: Discussionmentioning
confidence: 99%
“…This study reveals the positive influence of the EIReP in the preparation of TPVs and paves a new technology for the development of various types of TPVs in an eco‐friendly direction. The authors' earlier work reported the influence of three different peroxides36 and different co‐agents37 on 30:70 blend ratio of peroxide cured PP/EOC TPVs. The readers can refer the results of peroxide‐based TPVs to understand the divergence in the performance properties and morphological evolution.…”
Section: Discussionmentioning
confidence: 99%
“…The crosslinking density (D) was calculated according to the well-known Flory-Rehner equation as follows 26 : The samples before or after the UV-C aging that were weighed as m 0 were immersed in toluene at 20 C for 48 h to achieve the swelling equilibrium.…”
Section: Crosslinking Densitymentioning
confidence: 99%
“…G' is influenced also by morphology of the blends [28,37] . The morphology refinement and compatibility tend to increase the G' values.…”
Section: According To Thementioning
confidence: 99%